Ghana : Third Review Under the Extended Credit Facility Arrangement and Request for Waiver for Nonobservance of Performance Criteria, and Modifications of Performance Criteria-Press Release; Staff Report; and Statement by the Excutive Director for Ghana. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses Ghana's Third Review Under the Extended Credit Facility arrangement and Request for Waiver for Nonobservance of Performance Criteria (PCs), and Modifications of PCs. Program implementation in Ghana remains broadly satisfactory, but the economic outlook remains difficult and fiscal challenges are mounting. The growth outlook for 2016 and 2017 has weakened, mainly owing to disruptions in oil production, and non-oil economic activity is expected to remain subdued owing to continued fiscal consolidation and tight monetary policy. There was broad agreement with the authorities on the need to sustain a tight monetary stance given the still high inflation. The IMF staff recommends completion of the third review.